Safety assessment of L-ornithine oral intake in healthy subjects: a systematic review - Hyemin Yang; Yui Kuramochi; Sumika Sato; Ryosei Sakai; Kohsuke Hayamizu (Amino Acids)
Abstract L-Ornithine (L-Orn) is a nonessential amino acid but has many physiological roles. Accordingly, L-Orn has been used as a functional food or dietary supplement to ameliorate various maladies, but there is only limited information available about its safety. The safety of a chemical compound is generally assessed via non-clinical and clinical studies, but safety information derived from human studies is particularly important. Recently, systematic reviews have been used to assess the safety as well as the effectiveness and usefulness of such studies. Therefore, we conducted an assessment of the safety of L-Orn by systematically reviewing clinical studies. Specifically, we performed a comprehensive search of databases for clinical trials in which L-Orn was added to ordinary diets (i.e., orally administered) in healthy individuals. Focusing on PubMed, Cochrane Library, Ichushi-Web, and EBSCOhost, we comprehensively searched for reports on human studies on the oral ingestion of L-Orn. We identified 22 articles as subjects for this SR. Among these articles, the maximum L-Orn dose was 14,025 mg/person/day in the form of L-Orn hydrochloride and the maximum duration of administration was 156 days. The main observed adverse events were gastrointestinal disorders. Indexing these adverse events, the no observed adverse effect level was estimated to be 12,000 mg/person/day for L-Orn in the form of L-Orn hydrochloride. When we conducted an integration analysis on the risk of adverse events, the difference between those with and without L-Orn supplementation in the risk of gastrointestinal disorders was 0.00 (95% confidence interval: ±0.02, P = 1.00), so no significant effects were observed. (UMIN000033371)